Meningkatkan Kemampuan Kader Posyandu Lansia melalui Penerapan Latihan GELASE (GERAKAN BALANCE EXERCISE) - Ni Made Dwi Ayu Martini; Ni Luh Putu Dian Yunita Sari; Ketut Darmaja (Universitas Lancang Kuning, 2022)
The elderly experience decreased of muscle strength and balance which can lead to falls. Falls can be fatal and lead to death. So far, health programs have only focused on non-communicable diseases, so it is necessary to implement a program to prevent elderly from falls. GELASE exercise is an elderly physical exercise program that involves the lower limbs to improve its strength and balance. This program consisted of health education sessions, sharing sessions, exercises, and role play which were attended by five cadres and one community health centres nurse. The targets were given pre and post-program questionnaires and an evaluation form was carried out. It was known that all targets experienced an increase in knowledge and ability about the risk of falling and the GELASE exercise. It is important for the cadres to apply GELASE exercises regularly to the elderly group in their area.